Awareness of, and participation with, digital alcohol marketing, and the association with frequency of high episodic drinking among young adults. (3rd July 2016) - Critchlow, Nathan; Moodie, Crawford; Bauld, Linda; Bonner, Adrian; Hastings, Gerard
Abstract: Aim : To explore the association between awareness of traditional and digital marketing, participation with digital marketing and young adults' frequency of high episodic drinking (HED). Methods : An online cross-sectional survey of 18–25 year olds ( n = 405) measured awareness of nine traditional marketing channels, and awareness of, and participation with, 11 digital marketing channels. HED was measured using the final item from the Alcohol Use Disorders Identification Test – Consumption (AUDIT-C). Findings : Respondents, on average, were aware of alcohol being marketed through 4.30 traditional and 6.23 digital marketing channels, and had participated with marketing through 2.34 digital channels. Respondents who reported HED on at least a weekly basis reported the most awareness of, and participation with, alcohol marketing. Those who reported never engaging in HED, or doing so less than monthly, reported the lowest. Significant associations were found between awareness of, and participation with, traditional and digital alcohol marketing and increased frequency of HED. Conclusions : That digital marketing was more successful than traditional in reaching young adults, and had a stronger association with increased frequency of HED, highlights the dynamic nature of marketing communications and the need for further research to fully understand young people's experience with digital marketing.